2016
DOI: 10.1016/j.cca.2016.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Higher degree of glycation of hemoglobin S compared to hemoglobin A measured by mass spectrometry: Potential impact on HbA1c testing

Abstract: BACKGROUND Glycated hemoglobin (GHb), reported as HbA1c, is used as marker of long-term glycemia for diabetic patients. HbA1c results from boronate affinity methods are generally considered to be unaffected by most hemoglobin variants; this assumes comparable glycation of variant and non-variant (HbAA) hemoglobins. In this report, glycation of HbA beta chain (βA) and HbS beta chain (βS) for the most common Hb variant trait (HbAS) are examined. METHODS We analyzed 41 blood samples from subjects with HbAS, bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 11 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…Determination of HbA1c is performed using various analytical methods such as cation-exchange chromatography and capillary electrophoresis with optical detection as well as immunological methods . However, numerous studies have demonstrated that Hb sequence variants or other proteoforms (term used according to Smith and Kelleher) can lead to interferences in identification and quantification of HbA1c. Therefore, mass spectrometry (MS) has been considered as an alternative for unambiguous identification and quantification, not only for glycated Hb, but also for Hb sequence variants. Research has been focused on matrix-assisted laser desorption/ionization-MS and direct-infusion electrospray ionization-MS. , These studies demonstrated good correlation between clinically determined HbA1c values and individually glycated α- and β-chains.…”
mentioning
confidence: 99%
“…Determination of HbA1c is performed using various analytical methods such as cation-exchange chromatography and capillary electrophoresis with optical detection as well as immunological methods . However, numerous studies have demonstrated that Hb sequence variants or other proteoforms (term used according to Smith and Kelleher) can lead to interferences in identification and quantification of HbA1c. Therefore, mass spectrometry (MS) has been considered as an alternative for unambiguous identification and quantification, not only for glycated Hb, but also for Hb sequence variants. Research has been focused on matrix-assisted laser desorption/ionization-MS and direct-infusion electrospray ionization-MS. , These studies demonstrated good correlation between clinically determined HbA1c values and individually glycated α- and β-chains.…”
mentioning
confidence: 99%
“…Therefore, the glycosylation rate of β S appears to be higher than that of β A . However, Kabytaev et al (40) concluded that the clinical interpretation was relatively unaffected by the tiny net difference between HbAS (sickle phenotype) and uncharacterized total glycosylation. A summary of the altered glycosylation rates presented in mutants located in the first 10 amino acids of the β chain and at amino acid positions 139-140 is presented in Table II (41)(42)(43)(44).…”
Section: Interfering Factorsmentioning
confidence: 99%
“…Antibody based HbA 1c assays are principally not able to detect variants. Even variants which are prevalent in several populations have a direct or indirect influence on the measured HbA 1c what makes it desirable to gain knowledge about their presence [6,7].…”
Section: Introductionmentioning
confidence: 99%